Use-value assessment of rural lands : time for reform? - Anderson, John E. (John Edwin), 1951-; England, Richard W. (Policy focus series (Lincoln Institute of Land Policy), 2015)
Like its companion book, this report describes the history and design features of state use-value assessment (UVA) programs--the preferential assessment of rural land under the property tax. Anderson and England explain the theoretical underpinnings of land valuation and survey empirical studies of UVA implementation and impacts. They also identify the weaknesses of UVA programs and propose policy reforms to make the programs more effective and fair.